ACTIVITIES OF TAMURIAN MADRASAS IN KHURASAN IN THE WORKS OF HISTORICAL KHANDAMIR LIGHTING - Imomov Ulugbek; Murodov Xindolmirzo (Galaxy International Interdisciplinary Research Journal, 2021)
Khandamir Ghiyasiddin Muhammad ibn Burhaniddin Muhammad Sherazi is known as a mature historian and thinker of his time. During his lifetime, Khandamir wrote about 20 works, 8 of which have survived. Among the masterpieces such as "Ma’asir ul muluk", "Humoyunnoma", "Khulasat ul akhbor" are among the masterpieces. This article describes the madrasas built by such a mature scholar in Khorasan during the Timurids and the educational process in them.As a historian, Khandamir paid close attention to the special qualities of such madrasas, khanaqahs and hospitals.